2018
DOI: 10.1111/ajfs.12216
|View full text |Cite
|
Sign up to set email alerts
|

Non‐controlling Large Shareholders and Firm Performance in China

Abstract: This paper examines the determination of non-controlling large shareholders (NCLSs) on firm performance and investigates the impacts of NCLSs on tunneling and investment efficiency. We use three attributes of NCLSs (ownership, identity, and relational board/management representation) to fully capture the governance effects of NCLSs. We find robust evidence that NCLSs are associated with higher firm performance. Furthermore, we also document that NCLSs promote investment efficiency. However, except for individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 49 publications
0
16
0
6
Order By: Relevance
“…Shareholding ratio of the first shareholder (sr ) has a significant negative impact on innovation quantity and innovation quality. As supervisory regulations in the Chinese capital market are not yet sound, substantial shareholders usually employ the tunnel effect to achieve excess control and gain more private income (Yan & He, 2018). Firm innovation is a long‐term process with high risk and uncertainty.…”
Section: Results and Analysismentioning
confidence: 99%
“…Shareholding ratio of the first shareholder (sr ) has a significant negative impact on innovation quantity and innovation quality. As supervisory regulations in the Chinese capital market are not yet sound, substantial shareholders usually employ the tunnel effect to achieve excess control and gain more private income (Yan & He, 2018). Firm innovation is a long‐term process with high risk and uncertainty.…”
Section: Results and Analysismentioning
confidence: 99%
“…Previous research, so far, only tested the value of the relevance of OCI information in the income statement without involving earnings attribution policies (Saymeh, 2019;Elbakry et al, 2018;Banks et al, 2018;Shi and Zhou, 2017;Sajnog, 2017;Schaberl and Victoravich, 2015;Jones and Smith, 2011;Kanagaretnam et al, 2009). Research on earnings attribution has been carried out by Francesco (2018), Yan andHe (2018), andLopes (2013), but all three have not linked earnings attributions to OCI and the ability to predict future CIs.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Empirical evidence from a previous study shows that the presentation of earnings attributions is an effort to the transparency of financial statements (Yahaya, KA, Fagbemi, TO and Oyeniyi, 2015). It increases the value of financial statements related to financial performance assessment (Yan & He, 2018) and the principle of fairness and attention to the minority as well as affecting the market value of the company (Francesco, 2018) and returns (So & Smith, 2009). Presentation of the income statement in which there is additional information on OCI components, attributions of NI and OCI earnings to owners of the parent entity (majority shareholder) and noncontrolling interests (minority shareholders) will be more informative and quality (Chebaane & Ben, 2014), more transparent (Shi et al, 2017).…”
Section: Earnings Attribution To the Owner And Aggregate Comprehensive Incomementioning
confidence: 99%
See 1 more Smart Citation
“…This supervisory role is particularly pronounced in economies where investor protection is weak, as evidenced by extensive literature. Yan and He (2018) found that the presence of NCLS in Chinese-listed companies would improve the investment efficiency and corporate value of companies. In a study on the ownership structure of listed companies in China, Jiang et al (2017) found that, compared with companies controlled by a single shareholder, multiple large shareholders reduce agency costs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%